Quantitative measurement of the pupillary light reflex has independent prognostic value in patients resuscitated from cardiac arrest. (2nd May 2022) - Nyholm, B; Obling, L; Hassager, C; Grand, J; Moller, JE; Kjaergaard, J
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Novo Nordisk Foundation Background: Patients resuscitated from cardiac arrest (CA) are at high risk of unfavourable neurological outcome or death caused by anoxic brain injury. Bedside quantitative pupillometry are a promising new entity as part of the multimodal neuroprognostication. We aimed to evaluate the prognostic value of quantitative assessment of the percentage change in pupil size (%CH) in unconscious critically ill cardiac patients, both with or without CA. Methods: Patients admitted to our cardiac intensive care unit from April 2015 to June 2017, assessed with serial quantitative pupillometry until discharge or death, were included. Patients were divided into subgroups of out-of-hospital-cardiac arrest (OHCA), in-hospital cardiac arrest (IHCA), and of other unconscious critically ill non-CA cardiac patients. With median value as cut-off, we used Cox regression to assess the association between %CH and the hazard ratios (HR) of 30-day mortality. In all groups we used multivariable Cox models adjusted for age, sex, and event of ST elevation myocardial infarction (STEMI) and for OHCA and IHCA, we further adjusted for CA variables of shockable primary rhythm and time to return of spontaneous circulation (ROSC). Kaplan-Meier survival analysis were performed for all groups. Results: We included 221 patients (OHCA n=135, IHCA =28, and non-CA n=58), predominantly males, admitted with a mean age of 63±12 years (61±12 years for OHCA, 65±12 years for IHCA and 67±11 years for non-CA). We estimated the median %CH at 9.5% for OHCA, 11.0 for IHCA, and 13.0% for non-CA. In both CA groups, a %CH lower than the median were significantly (p<0.05) associated with an increased HR of 30-day mortality in univariate analysis. For OHCA patients, Cox regression yielded a HR of 2.5 with a 95% confidence interval (95% CI) of 1.346-4.542 in the unadjusted model, and a HR at 2.4 with 95% CI: 1.3-4.5 in the adjusted model. When adjusting for shockable primary rhythm and time to ROSC in the OHCA group HR remained significant at 2.4 with 95% CI: 1.2-4.7. In the IHCA group we found HR at 3.7 with 95% CI: 1.0-14.1 in both the unadjusted and adjusted model. However, results were borderline significant (p=0.052 and p=0.078, respectively). When adjusting for shockable primary rhythm and time to ROSC in the IHCA group the HR was 4.5, however with 95% CI: 0.4-46.1 and p=0.208. The non-CA group HR was 0.7 with 95% CI: 0.3-1.8 (unadjusted) and HR 0.7 with CI: 0.3-1.9 (adjusted), with p=0.470 and p=0.483, respectively. Kaplan-Meier curves presented significantly higher mortality in patients with %CH lower than the median for OHCA and IHCA. No significant risk was found for non-CA (p=0.510). Conclusion: A %CH below 9.5% is independently and significantly associated with increased risk of death in patients resuscitated from OHCA. Further analyses may focus on identifying optimal cut-offs and further compare the prognostic information of different parameters in quantitative pupillometry.